Performance optimization of pharmaceutical supply chain by a unique resilience engineering and fuzzy mathematical framework. Issue 5 (23rd April 2020) - Salehi, Vahid; Salehi, Razieh; Mirzayi, Mahsa; Akhavizadegan, Faezeh
Abstract: Pharmaceutical supply chains (PSCs) are responsible for guaranteeing that the right people receive the right medication at the right time and in the right conditions. These responsibilities make PSC very complex and subsequently increase their vulnerability and disturbance probability. Resilience engineering (RE) can enable supply chain managers to cope with disruptions and to help them maintain their efficient performance. This study proposes a unique RE framework for performance optimization of the pharmaceutical sector in a veterinary organization. A standard questionnaire was used to collect the required data. Next, data envelopment analysis (DEA) and fuzzy data envelopment analysis (FDEA) approaches were employed to formulate the problem. Sensitivity analysis was performed based on the most appropriate model of DEA and FDEA. The results showed that redundancy was the most effective factor in enhancing efficiency in PSCs in the veterinary organization. This is one of the first studies that investigate the influence of resilience indicators on PSC through DEA/FDEA and statistical methods.